Design and manufacturing of skins based on composite corrugated laminates for morphing aerodynamic surfaces. (9th March 2017) - Airoldi, Alessandro; Fournier, Stephane; Borlandelli, Elena; Bettini, Paolo; Sala, Giuseppe
Abstract: The paper discusses the approaches for the design and manufacturing of morphing skins based on rectangular-shaped composite corrugated laminates and proposes a novel solution to prevent detrimental effects of corrugation on aerodynamic performances. Additionally, more complex corrugated shapes are presented and analysed. The manufacturing issues related to the production of corrugated laminates are discussed and tests are performed to compare different solutions and to assess the validity of analytical and numerical predictions. The solution presented to develop an aerodynamically efficient skin consists in the integration of an elastomeric cover in the corrugated laminate. The related manufacturing process is presented and assessed, and a fully nonlinear numerical model is developed and characterized to study the behaviour of this skin concept in different load conditions. Finally, configurations based on combinations of individual rectangular-shaped corrugated panels are considered. Their structural properties are numerically investigated by varying geometrical parameters. Performance indices are defined to compare structural stiffness contributions in non-morphing directions with the ones of conventional panels of the same weight. Numerical studies also show that the extension of the concept to complex corrugated shapes may improve both the design flexibility and some specific performances with respect to rectangular shaped corrugations. The overall results validate the design approaches and manufacturing processes to produce corrugated laminates and indicate that the solution for the integration of an elastomeric cover is a feasible and promising method to enhance the aerodynamic efficiency of corrugated skins.